In vitro cytotoxicity and induction of apoptosis by silica nanoparticles in human HepG2 hepatoma cells - Lu X (Dove Medical Press, 2011)
Xun Lu2,3, Jiangchao Qian1, Huanjun Zhou2,3, Qi Gan2,3, Wei Tang1, Jingxiong Lu3, Yuan Yuan1,2, Changsheng Liu1–31State Key Laboratory of Bioreactor Engineering, 2Key Laboratory for Ultrafine Materials of Ministry of Education, 3Engineering Research Center for Biomedical Materials of Ministry of Education, East China University of Science and Technology, Shanghai, People’s Republic of ChinaBackground: Silica nanoparticles have been discovered to exert cytotoxicity and induce apoptosis in normal human cells. However, until now, few studies have investigated the cytotoxicity of silica nanoparticles in tumor cells.Methods: This study investigated the cytotoxicity of 7–50 nm silica nanoparticles in human HepG2 hepatoma cells, using normal human L-02 hepatocytes as a control. Cell nucleus morphology changes, cellular uptake, and expression of procaspase-9, p53, Bcl-2, and Bax, as well as the activity of caspase-3, and intracellular reactive oxygen species and glutathione levels in the silica nanoparticle-treated cells, were analyzed.Results: The antitumor activity of the silica nanoparticles was closely related to particle size, and the antiproliferation activity decreased in the order of 20 nm > 7 nm > 50 nm. The silica nanoparticles were also cytotoxic in a dose- and time-dependent manner. However, the silica nanoparticles showed only slight toxicity in the L-02 control cells, Moreover, in HepG2 cells, oxidative stress and apoptosis were induced after exposure to 7–20 nm silica nanoparticles. Expression of p53 and caspase-3 increased, and expression of Bcl-2 and procaspase-9 decreased in a dose-dependent manner, whereas the expression of Bax was not significantly changed.Conclusion: A mitochondrial-dependent pathway triggered by oxidative stress mediated by reactive oxygen species may be involved in apoptosis induced by silica nanoparticles, and hence cytotoxicity in human HepG2 hepatic cancer cells.Keywords: silica nanoparticles, cytotoxicity, apoptosis, HepG2 cells, mitochondrial-dependent pathway, oxidative stress